2022
DOI: 10.1038/s41598-022-13522-5
|View full text |Cite|
|
Sign up to set email alerts
|

Gain and isolation enhancement of a wideband MIMO antenna using metasurface for 5G sub-6 GHz communication systems

Abstract: This work proposes a compact metasurface (MS)-integrated wideband multiple-input multiple-output (MIMO) antenna for fifth generation (5G) sub-6 GHz wireless communication systems. The perceptible novelty of the proposed MIMO system is its wide operating bandwidth, high gain, lower interelement gap, and excellent isolation within the MIMO components. The radiating patch of the antenna is truncated diagonally with a partially ground plane, and a metasurface has been employed for enhancing the antenna performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The proposed four-port MIMO shows isolation >18.5 dB which is larger compared to the works reported in [6, 11, 14, 15, 16, 24, 25]. This is achieved by introducing a pair of interconnected inverted L-stubs of asymmetric lengths.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The proposed four-port MIMO shows isolation >18.5 dB which is larger compared to the works reported in [6, 11, 14, 15, 16, 24, 25]. This is achieved by introducing a pair of interconnected inverted L-stubs of asymmetric lengths.…”
Section: Resultsmentioning
confidence: 74%
“…It shows an average out-of-band rejection level of 15 dB in the frequency ranging from 6 to 20 GHz, thereby enhancing the stopband behavior of the antenna resulting in a high signal-to-noise ratio. The proposed four-port MIMO shows isolation >18.5 dB which is larger compared to the works reported in [6, 11, 14, 15, 16, 24, 25]. This is achieved by introducing a pair of interconnected inverted L-stubs of asymmetric lengths. The center-to-center spacing between the adjacent elements in the four-port MIMO antenna is reduced within the range of 0.22 λ e to 0.25 λ e which is smaller than [6, 10, 11, 15, 16, 24, 25]. The effect of interconnected ground planes has an inevitable impact on isolation.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The initial circular patch antenna of 28 GHz is calculated using the well-known formula [20]. It was reported that the etching of the slots in the diagonal corners of the antenna patch can improve the impedance bandwidth [21]. Therefore, in the antenna design, the circle patch is etched by two equal circle shapes in the diagonal patch printed on Roger substrate backed with a continuous copper ground plane, as shown in Figure 1(a) (referred to as Ant.…”
Section: Antenna Designmentioning
confidence: 99%
“…Fifth-generation technology increases channel capacity with more bandwidth per carrier (from 5 to 400 MHz) [ 40 ], being spectrally more efficient due to the higher orders of the modulation schemes [ 41 , 42 ]. Previously employed in 4G, the multiple-input multiple output (MIMO) technique simultaneously uses multiple antennas with multiple channels for signal transmission and reception, increasing channel bandwidth and maintaining antenna efficiency without requiring additional power [ 43 , 44 ]. Antenna gains in the MMIMO (massive MIMO) version used in 5G compensate for channel propagation losses by providing robustness against interference and low latency [ 45 ].…”
Section: Introductionmentioning
confidence: 99%